Tissue distribution of heavy metals (Cd, Cu, Pb and Zn) in the greenlipped mussel perna viridis from Nenasi and Kuala Pontian, East Coast of Peninsular Malaysia - Yap, Chee Kong; Cheng, Wan Hee; Ismail, Ahmad; Tan, Soon Guan (Universiti Putra Malaysia Press, 2005)
Previous studies reported that the green-lipped mussel Perna viridis were widely found on the west coast of Peninsular Malaysia but not on the east coast of the Peninsula. In this study, surveys and sampling were conducted from Tumpat to Mersing in April 2004, but the mussels were only found at Nenasi and Kuala Pontian in Pahang coastal waters. Therejare, from this study, we confirm that the mussels on the east coast were not as widely found as on the west coast of Peninsular Malaysia. The mussel samples collected were analysed for cadmium (Cd), copper (Cu), lead (Pb) and zinc (Zn) and the metal concentrations (J.lg/g dry weight) were 1.892.13, 3.84-10.34, 7.95-8.84 and 93.1-119.6 far Cd, Cu, Pb and Zn, respectively. These results indicate that Kuala Pontian samples accumulated higher concentrations of Cu (in remaining soft tissue and mantle) and Zn (in remaining soft tissue, mantle and muscle) compared to those in Nenasi while Cd and Pb showed no significant difference (P> 0.05) between the two sample sites. Since there were no observable anthropogenic inputs ar activities at the two sampling sites, the variation of metal concentrations accumulated in the soft tissues could be mostly attributable to the significant difference in size (shell length, and shell width) and salinity of the two sites. The other environmental factars could also cause differences in the metal bioavailabilities in the coastal waters that were reflected in different concentrations accumulated in the different soft tissues of the mussels.